Solitary Plasmacytoma of the Cecum and the Ascending Colon: Surgical Resection as a Treatment Modality. (12th April 2015) - Dalgic, Tahsin; Bostanci, Erdal Birol; Cakir, Tebessum; Ozer, Ilter; Ulas, Murat; Aydog, Gulden; Akoglu, Musa
Abstract : Colonic solitary plasmacytoma is a rare disease, with few reports occurring in the literature. Solitary plasmacytoma is defined as a plasma cell tumour with no evidence of bone marrow infiltration. Plasmacytoma can present as a solitary tumour in bone or in other parts of the body. The gastrointestinal tract is rarely the site of the disease. We report on the case of a 51-year-old man presenting with a colonic symptomatic mass with unclear biopsy results. A resected specimen showed a solitary plasmacytoma. Surgical resection was an adequate treatment modality in this case. Endoscopic resection, radiotherapy, and chemotherapy are also preferred treatments in selected gastrointestinal plasmacytoma cases.